Hydraulics and life history of tropical dry forest tree species: coordination of species' drought and shade tolerance - Markesteijn, Lars; Poorter, Lourens; Bongers, Frans; Paz, Horacio; Sack, Lawren (The New phytologist, 2011)
Plant hydraulic architecture has been studied extensively, yet we know little about how hydraulic properties relate to species' life history strategies, such as drought and shade tolerance. The prevailing theories seem contradictory. We measured the sapwood (K s ) and leaf (K l ) hydraulic conductivities of 40 coexisting tree species in a Bolivian dry forest, and examined associations with functional stem and leaf traits and indices of species' drought (dry-season leaf water potential) and shade (juvenile crown exposure) tolerance. Hydraulic properties varied across species and between life-history groups (pioneers vs shade-tolerant, and deciduous vs evergreen species). In addition to the expected negative correlation of K l with drought tolerance, we found a strong, negative correlation between K l and species' shade tolerance. Across species, K s and K l were negatively correlated with wood density and positively with maximum vessel length. Consequently, drought and shade tolerance scaled similarly with hydraulic properties, wood density and leaf dry matter content. We found that deciduous species also had traits conferring efficient water transport relative to evergreen species. Hydraulic properties varied across species, corresponding to the classical trade-off between hydraulic efficiency and safety, which for these dry forest trees resulted in coordinated drought and shade tolerance across species rather than the frequently hypothesized trade-off.